2020
DOI: 10.1101/2020.07.21.213504
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neuronal SKN-1B Modulates Nutritional Signalling Pathways and Mitochondrial Networks to Control Satiety

Abstract: The feeling of hunger or satiety results from integration of the sensory nervous system with other physiological and metabolic cues. This regulates food intake, maintains homeostasis and prevents disease. In C. elegans, chemosensory neurons sense food and relay information to the rest of the animal via hormones to control food-related behaviour and physiology. Here we identify a new component of this system, SKN-1B which acts as a central food-responsive node, ultimately controlling satiety and metabolic homeo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 69 publications
(143 reference statements)
0
6
0
Order By: Relevance
“…Expression levels of daf-7 have been previously linked to activation of the guanylate cyclase DAF-11 in ASI neurons during starvation 24 . We therefore asked whether DAF-11 is also required for UPR ER activation upon 1-undecene exposure, and observed that DAF-11 was indeed necessary for transcriptional upregulation of xbp-1s and the XBP-1 target gene Y41C4A.11 (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Expression levels of daf-7 have been previously linked to activation of the guanylate cyclase DAF-11 in ASI neurons during starvation 24 . We therefore asked whether DAF-11 is also required for UPR ER activation upon 1-undecene exposure, and observed that DAF-11 was indeed necessary for transcriptional upregulation of xbp-1s and the XBP-1 target gene Y41C4A.11 (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…SKN-1B, in contrast to the A and C isoforms is expressed specifically in the chemosensory ASI neurons and lacks functionally important features of other SKN-1 isoforms including the crucial DIDLID motif [ 67 ]. This isoform has also been implicated in the remodelling of mitochondrial networks in another tissue, the muscle, suggesting that cell non-autonomous signaling downstream of SKN-1B has profound physiological effects in a distant tissue [ 74 ]. Thus, SKN-1 responds to a broad range of stresses in an isoform specific manner.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, foraging behaviour is impaired in animals with null mutations in skn-1 , with skn-1 animals remaining on limited food when wild-type animals would instead choose to forage for more abundant food [ 75 ]. Recent work directly attributes this reduction in exploratory behaviour to SKN-1B, demonstrating that a null allele specific for that isoform recapitulates this foraging defect and that transgenic rescue of skn-1b rescues foraging behaviours [ 74 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations